2022
DOI: 10.1111/jocn.16217
|View full text |Cite
|
Sign up to set email alerts
|

Use of virtual reality in managing paediatric procedural pain and anxiety: An integrative literature review

Abstract: Aims: This integrative review aimed to identify, analyse and synthesise studies investigating the clinical efficacy of virtual reality (VR) distraction for children undergoing varying painful and anxiety-inducing medical procedures across different hospital settings and to identify implications for research and clinical practice.Background: Virtual reality has been leveraged as a distraction tool in the healthcare setting to help patients manage procedural pain and anxiety. Initial studies in the burn wound ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 135 publications
2
29
0
Order By: Relevance
“…14 VR software that has been used in distraction therapy for pain includes VR experiences such as a rollercoaster ride, swimming underwater, travelling around the world, and enjoying nature. 15 VR programs studied that involved people with autism spectrum disorder include simulations that aim to teach various skills such as driving, interviewing, supermarket shopping, and emotion recognition. 10,16 Some VR interventions involve commercially available games, whereas others use games developed specifically for health applications.…”
Section: The Technologiesmentioning
confidence: 99%
See 3 more Smart Citations
“…14 VR software that has been used in distraction therapy for pain includes VR experiences such as a rollercoaster ride, swimming underwater, travelling around the world, and enjoying nature. 15 VR programs studied that involved people with autism spectrum disorder include simulations that aim to teach various skills such as driving, interviewing, supermarket shopping, and emotion recognition. 10,16 Some VR interventions involve commercially available games, whereas others use games developed specifically for health applications.…”
Section: The Technologiesmentioning
confidence: 99%
“…40 Children A 2022 systematic review evaluated the use of VR distraction for pain and anxiety during medical procedures in pediatric patients. 15 The systematic review included a total of 77 studies (59 randomized controlled trials, 6 interventional/observational studies, 3 quasiexperimental studies, 2 cross-sectional studies, 1 retrospective chart review, and 6 case reports) that evaluated VR distraction in 2,174 patients aged from 6 months to 18 years undergoing medical procedures in a variety of settings. 15 The medical procedures in the included studies were burn wound care procedures, postburn injury physiotherapy, dental procedures, needle-related procedures, and other procedures.…”
Section: Summary Of the Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Virtual reality (VR) is a technology based on recreating an artificial three-dimensional interactive environment, in which the user has the illusion of movement. Several studies investigating the effect of VR during painful or distressing procedures have been conducted in adults and children [3,4]. Although VR interventions are not standardized, most available studies showed some effects on pain, with a high safety profile and high patient satisfaction [5,6].…”
Section: Introductionmentioning
confidence: 99%